Curtin-Hammett Paradigm for Stereocontrol in Organocatalysis by Diarylprolinol Ether Catalysts - Bures,J; Armstrong,A; Blackmond,DG (JOURNAL OF THE AMERICAN CHEMICAL SOCIETY, 2012)
Detailed mechanistic study of two reactions catalyzed by diarylprolinol ether catalysts, the conjugate addition of aldehydes to nitro-olefins and the alpha-chlorination of aldehydes, leads to the proposal that the stereochemical outcome in these cases is not determined by the transition state of the step in which the stereogenic center is formed from enamine attack on the electrophile but instead is correlated with the relative stability and reactivity of diastereomeric intermediates downstream in the catalytic cycle. This combination of kinetic and thermodynamic factors illustrates a remarkable Curtin-Hammett scenario that can result in either an enhancement or an erosion of the selectivity that would be predicted by the transition state for enamine attack on the electrophile. Evidence is offered to suggest that this concept may represent a general phenomenon for pyrrolidine-based catalysts lacking an acidic directing proton. Implications for catalyst and reaction design are discussed.